Ethno-botanical Wild Food Plants of Jaunsar - Bawar (Western Himalaya) , Uttaranchal - Pundir, Y. P. S.; Singh, Dhan (Indian Forester, 2002)
The paper reports forty wild edible food plants used by the natives of Jaunsar - Bawar tribal area. A list of 137 more wild food plants already reported from this area by the authors is also given.